Drawn from Nature: Wallpaper patterns in New Zealand's Schools of Art and Design - Forster-Garbutt, Eva (Architectural History Aotearoa, 2023)
Schools of art and design were established in New Zealand from 1870 to foster the development of technical skills in the trades and the creative and decorative arts. These schools flourished throughout the latter two decades of the nineteenth century and the early decades of the twentieth century. Informed by the teachings of the South Kensington School in England, students in New Zealand were instructed in the design of patterns for interior finishes, such as wallpapers, tiles, linoleum and textiles. The blossoming Arts and Crafts movement not only guided the teaching models of these schools, but encouraged students to explore the graphic possibilities of flora and fauna, which in the New Zealand context resulted in original decorative patterns with native motifs. This paper will explore the design of wallpaper patterns by students at the New Zealand schools of art, focusing on those produced between the mid-1880s and the late 1890s. The influence and inspiration for these patterns will be traced, from the Arts and Crafts movement, the teaching methods at schools of art and design, to the natural New Zealand environment.